The Incidence of At-Risk Students in Indiana: A Longitudinal Study - Randall S. Vesely (Educational Considerations, 2010)
Elementary and secondary students can be impacted by a number of risk factors, all of which can have a negative influence on their academic success.
Keywords: At-Risk Students; risk factors; incidence; Indiana; longitudinal study; educational programs; community; programs; variables; procedures; disabilities